Assessing the challenges affecting the investigative methods to combat online child exploitation material offenses. (November 2020) - Holt, Thomas J.; Cale, Jesse; Leclerc, Benoit; Drew, Jacqueline
Abstract: Technology has dramatically simplified the process of engaging in a variety of crimes, particularly the distribution of child exploitation materials, or CEM. The ability to share photos and video across the globe through high speed Internet connections and mobile devices has made it easy to access CEM. At the same time, technology has complicated the investigation of these crimes by increasing the scope of spaces to police that is operated by public and private entities. This review outlines the challenges inherent in the investigation of CEM in the context of Wall's typology of policing online spaces, recognizing formal and informal sources of social control. The methods used by law enforcement to affect CEM are discussed, highlighting current limitations inherent in online investigations; namely the sheer scope of the problem and the nexus between rapid technological advances and commensurate legal responses, among others. The review highlights the need for engagement from industrial and non-governmental organizations in addition to law enforcement in order to facilitate the investigation of CEM offenses; strategies to improve the state of policing CEM need to include integrating public and private sphere responses to these offenses. Highlights: The Internet fosters immediate, persistent distribution of child exploitation materials. Police powers are limited compared to those of private industry in online spaces. Constant industry responses to CEM may affect police legitimacy over time. Better cooperation is needed across private industry and law enforcement.